INDÍGENAS COM DEFICIÊNCIA NA ESCOLA: UM ESTUDO SOBRE A INCLUSÃO NAS ALDEIAS DE UMARIAÇU I E II, NO MUNICÍPIO DE TABATINGA – AMAZONAS - OLIVEIRA, FRANCISCA FRANCIELIS AZEVEDO MAFRA DE (2020)
In this research, it was proposed to investigate how the inclusion of indigenous people with disabilities occurs in schools in the villages of Umariaçu I and II, in the municipality of Tabatinga - Amazonas. People with disabilities are those who have long-term physical, mental, intellectual or sensory impairments, which, in interaction with one or more barriers, can obstruct their full and effective participation in society on equal terms with other people.The question that generated this research is precisely to know how the process of inclusion and schooling of indigenous people with disabilities occurs.The objectives of this research were: (i) To investigate the factors that hinder teaching from an inclusive perspective and the acquisition of learning by students with disabilities in village schools; (ii) Describe how the inclusion and education of indigenous people with disabilities occurs; (iii) Discuss the challenges for the implementation of Specialized Educational Assistance in schools in these villages.The choice for this theme came from the empirical observation of the incidence of disabilities in villages in the indigenous community, as well as the constant complaints of teachers, in relation to the lack of professional qualification to serve this clientele of students, in addition to personal experiences as a teacher, who evidence the inevitability of confronting discriminatory exclusionary practices and creating alternatives to overcome them An attempt was also made to approach indigenous education and indigenous school education, emphasizing that both one and the other constitute two different ways of educating. The theoretical framework that supported this research comprises the works carried out in the area of inclusive education based on: Sassaki, Mantoan, Mazzotta and by authors dealing with indigenous education and culture such as: Grupioni, Feitosa, Cremonezze, Soares, Oliveira Filho, among others. It is a research with a qualitative approach, of an investigative nature, but, in some moments, the quantitative approach is used. The case study of indigenous people with disabilities enrolled in two municipal schools was used as a method. The data collection procedure consisted of direct contact, carried out on the spot, which made it possible to make a situational diagnosis of the local reality. It was also used the resource of the individual interview with questionnaires directed to the managers, coordinators and teachers, in addition to documentary analysis directly from the school departments. From the data obtained with this study, it can be highlighted that, among so many difficulties existing in the school context, there is a lack of preparation by teachers, as well as a lack of infrastructure in schools. Most teachers do not feel prepared to deal with the diversity and specificities of each student and the schools did not make a physical restructuring so that they would be able to receive this clientele of students. In relation to the existing and implemented public policies, the hypotheses that they have not been adopted in an adequate way to guarantee the access and the permanence of indigenous people with disabilities in school, are confirmed, despite being insufficient what is expected to be guaranteed a real school inclusion. Only the laws do not account for the inclusion process, there must be, in addition to them, human, pedagogical and physical conditions and resources for the proposed laws to be applied with really significant results. Thus, it is hoped that this research can contribute with relevant and significant data so that the act of including becomes a more constant practice in indigenous schools.